Forests growing under dry conditions have higher hydrological resilience to drought than do more humid forests. (25th November 2016) - Helman, David; Lensky, Itamar M.; Yakir, Dan; Osem, Yagil
Abstract: More frequent and intense droughts are projected during the next century, potentially changing the hydrological balances in many forested catchments. Although the impacts of droughts on forest functionality have been vastly studied, little attention has been given to studying the effect of droughts on forest hydrology. Here, we use the Budyko framework and two recently introduced Budyko metrics ( deviation and elasticity ) to study the changes in the water yields (rainfall minus evapotranspiration) of forested catchments following a climatic drought (2006–2010) in pine forests distributed along a rainfall gradient (P = 280–820 mm yr −1 ) in the Eastern Mediterranean (aridity factor = 0.17–0.56). We use a satellite‐based model and meteorological information to calculate the Budyko metrics. The relative water yield ranged from 48% to 8% (from the rainfall) in humid to dry forests and was mainly associated with rainfall amount (increasing with increased rainfall amount) and bedrock type (higher on hard bedrocks). Forest elasticity was larger in forests growing under drier conditions, implying that drier forests have more predictable responses to drought, according to the Budyko framework, compared to forests growing under more humid conditions. In this context, younger forests were shown more elastic than older forests. Dynamic deviation, which is defined as the water yield departure from the Budyko curve, was positive in all forests (i.e., less‐than‐expected water yields according to Budyko's curve), increasing with drought severity, suggesting lower hydrological resistance to drought in forests suffering from larger rainfall reductions. However, the dynamic deviation significantly decreased in forests that experienced relatively cooler conditions during the drought period. Our results suggest that forests growing under permanent dry conditions might develop a range of hydrological and eco‐physiological adjustments to drought leading to higher hydrological resilience. In the context of predicted climate change, such adjustments are key factors in sustaining forested catchments in water‐limited regions.